The Correlation of Maternal Childbirth Experience Satisfaction with Postnatal Depression, Anxiety and Stress Scoring - Al-kubaisi, Muna Khaleel; Radeef, Ali S; Ismail, Hamizah (International Journal of Innovative Research in Medical Science, 2019)
Aim: To evaluate the relationship of childbirth satisfaction and maternal postnatal emotional disturbances and to explore the social-demographic factors that affects the maternal childbirth experience. Methods: The study was performed at Hospital Ampuan Afzan in Kuantan, Pahang, Malaysia. All women presented with labour or elective caesarean sections (CS) at term were counselled to participate in the study. A total number of 600 participants were recruited. Elective CS perform in 99 patients and vaginal delivery achieved by 320 mothers, 40 ended by instrumental delivery and 141 went through emergency CS. Patients were interviewed 24 hours postnatal using two questionnaires; childbirth satisfaction questionnaire and DASS21 for psychological assessment. The data were analysed using possible correlation matrix in SPSS 23 version. Results: Pearson correlation test; Satisfaction had an inverse relation with depression scores (r = -0.14, n = 600, p = 0.001), anxiety (r = -0.125, n = 600) (p = 0.002), and stress (r = -0.116, n = 600, p = 0.005). Independent sample t-test; Women with satisfaction score below the mean (<66.01) have higher depressive mood (4.66 ± 5.31) than women with satisfaction score above the mean (≥66.01) (3.69 ± 5.40) (p<0.03). The same significant relation was seen with stress score (8.91 ± 7.27 and 7.78 ± 7.01 respectively) (p <0.05) but not with anxiety. Mothers who deliver first child (Primiparous) have lower satisfaction than women with previous delivery experience (Multiparous) (64.99 ± 6.31 and 66.70 ± 6.45 respectively) (p < 0.05) and women with neonates admitted to neonatal intensive care (65.08 ± 6.52 and 66.70 ± 6.42 respectively) (p < 0.05) are more liable to have dissatisfaction. Women delivered by elective caesarean section (CS) or instrumentation have lower satisfaction score than normal delivery and emergency CS (p < 0.05). Conclusion: Negative psychological background of mothers affects the level of maternal satisfaction post-childbirth. Primiparous mothers are dissatisfied with childbirth as compared with multiparous women. Neonatal admission to the Intensive Care Unit (NICU) negatively affects maternal satisfaction. Mothers with higher education have better satisfaction score.